Implementation of 85% health warning labels in India: advocacy success factors - Caitlin Weiger; Connie Hoe; Joanna Cohen (Tobacco Induced Diseases, 2018)
Background Tobacco control policies are critical to tackling the global tobacco epidemic. Unfortunately, little research has documented the factors that facilitate the implementation of tobacco control policies in low- and middle-income countries. In this study, we explored tactics and arguments used in India to advocate for the implementation of the 2014 rules increasing the size of pictorial health warning labels (HWLs) on tobacco products from 20% to 85% of the principle display area.